2023
DOI: 10.1038/s41598-023-47084-x
|View full text |Cite
|
Sign up to set email alerts
|

A computational approach to investigating facial attractiveness factors using geometric morphometric analysis and deep learning

Takanori Sano,
Hideaki Kawabata

Abstract: Numerous studies discuss the features that constitute facial attractiveness. In recent years, computational research has received attention because it can examine facial features without relying on prior research hypotheses. This approach uses many face stimuli and models the relationship between physical facial features and attractiveness using methods such as geometric morphometrics and deep learning. However, studies using each method have been conducted independently and have technical and data-related lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 67 publications
3
3
0
Order By: Relevance
“…We constructed a model that generates facial images using only a small amount of data. During the generation process, as the attractiveness score increased, morphological features such as suspended eyes and raised eyebrows changed, and the trends of these features were consistent with those reported in a previous study (Sano & Kawabata, 2023). The larger the input for the dominance score, the larger the face, which corresponds to the relationship between the face width and dominance (Carré & McCormick, 2008).…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…We constructed a model that generates facial images using only a small amount of data. During the generation process, as the attractiveness score increased, morphological features such as suspended eyes and raised eyebrows changed, and the trends of these features were consistent with those reported in a previous study (Sano & Kawabata, 2023). The larger the input for the dominance score, the larger the face, which corresponds to the relationship between the face width and dominance (Carré & McCormick, 2008).…”
Section: Discussionsupporting
confidence: 85%
“…Visual inspections of the results showed that morphological features such as contour sharpness and eyebrow angle changed when the impression of attractiveness was manipulated as the input value. Features such as sharply angled contours and elevated eyebrows were confirmed as attractive, which was consistent with the previous study (Sano & Kawabata, 2023). Additionally, manipulating the dominance impression as the input value resulted in changes in the morphological feature of face width; a previous report has also noted a relationship between facial width and aggression (Carré & McCormick, 2008).…”
Section: Studysupporting
confidence: 89%
See 3 more Smart Citations